Emission Performance of a Diesel Engine Fuelled with Petrol Diesel, Green Diesel, and Waste Cooking Oil Blends - O. Chiavola; E. Recco (Journal of Combustion)
The purpose of this paper is to conduct an experimental research on the impact of mixing ratio of biodiesel from waste cooking oil and an innovative diesel fuel (in which a renewable component is contained) on the emissions of an up-to-date light and compact small engine that has a leading role in city cars and urban vehicles. Two blends’ mixing ratios (20% and 40% by volume) were tested and the results were compared to those obtained when the engine was operated with low sulfur diesel (ULSD) and ULSD blended with 15% by volume of renewable diesel. The results indicate that diesel+ enhances CO and HC emissions in the exhaust as regards ULSD. Blending diesel+ with WCO causes a further reduction for most of the engine operative field. Concerning particulate emission, accumulation mode dominates for all fuels. Diesel+ is always characterized by lower mean diameters as regards ULSD. The addition of WCO further reduces the court mean diameter. Particle number concentration obtained by fuelling the engine with B40 is the lowest as regards all the other tested fuels. Concerning NOx, a moderate increase of the emission was observed when fuelling the engine with diesel+, net or in blends.